Hubungan antara Berat Badan, Diet, Aktivitas Fisik dan Tingkat Stres dengan Gangguan Siklus Menstruasi - Welstin Wemi Loa; Engelina Nabuasa; Amelya B. Sir (Universitas Nusa Cendana, 2022)
Menstrual cycle disorder is a disorder experienced by a woman during the menstrual period, characterized by prolongation of the menstrual cycle (oligomenorrhea), shortening of the menstrual cycle (polimenorrhea) or the absence of menstruation for 3 to 6 consecutive months (secondary amenorrhea), even non-occurrence menstruation after going through puberty (primary amenorrhea). This study aims to analyze the relationship between body weight, diet, physical activity and stress levels with menstrual cycle disorders in Faculty of Medicine University of Nusa Cendana students. This type of research is a quantitative study using a cross-sectional study approach. The study population was all 154 medical students class 2017-2019 and the sample was determined by using simple random sampling technique as many as 111 people. The data analysis used was univariate and bivariate analysis using the Chi-square test. The results showed that there was a relationship between body weight, physical activity and stress level with menstrual cycle disorders and there was no relationship between diet and menstrual cycle disorders. It is recommended that Faculty of Medicine University of Nusa Cendana students prevent menstrual cycle disorders from now on by maintaining a normal body weight, doing physical activity according to the body's needs and being able to manage stress, especially academic stress during their education.